Nanometer-scale ordered arrangement of diamond nanoparticles on substrates via electrostatic deposition. (23rd April 2021) - Yoshikawa, Taro; Liu, Ming; Miyake, Hiroto; Ieki, Ryosuke; Kojima, Ryouta; Makino, Yuto; Tsurui, Akihiko; Mahiko, Tomoaki; Nishikawa, Masahiro
Abstract: We demonstrate a nanometer-scale ordered arrangement of diamond nanoparticles (DNPs) on SiO2 surfaces via the technique of electrostatic deposition. Using the lift-off process combining electron beam lithography and surface functionalization with 3-aminopropyltriethoxysilane, the negative zeta potential of SiO2 surfaces are locally inversed to positive. Consequently, the DNPs are deposited on the limited SiO2 surface areas with ≥100 nm pitch line-and-space and dot array patterns where the electrostatic attractive interaction works. Since this approach does not rely on any specific material property other than zeta potential, it would be applicable to any material combination of charged nanoparticles and substrates.